(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
PurposeThe purpose of this study to find out the level of shyness between urban and ruralfemale athletes of district bijnor (up). MethodFor this study investigator had selected twenty five (N=25)urban female athletes and twenty five (N=25) female rural athletes who represent district in state leveltournament. The age of the subject ranged from 17 to 25years. The purposive sampling technique wasused to select the subject. t – test was employed to compare the level of shyness between urban andrural female athletes. For testing the hypothesis, the level of significance was set at 0.05.ResultTo find out their level of shyness, shyness scale developed by cheek Melichor (1985) wasadministered. Result of the study revealed significant difference on level of shyness between rural andurban players. Rural Female athletes are more shy comparison to urban players.Conclusions It is concluded from the findings that significant difference between rural and urban femaleathletes on the level of shyness.